A Digital Pressure Meter Equipped with Pressure Leak Detection - Septian Nur Wahyu Erdyansyah; Torib Hamzah; Dyah Titisari (Jurusan Teknik Elektromedik, POLTEKKES KEMENKES Surabaya, Indonesia, 2021)
A manual sphygmomanometer is an instrument used to measure blood pressure, and consists of an inflatable cuff, a mercury manometer (or aneroid gauge) and an inflation ball and gauge. To assess the condition, accuracy and safety of mercury and anaeroid sphygmomanometers in use in general practice and to pilot a scheme for sphyg- momanometer maintenance within the district. Therefore, it must be calibrated periodically. Using the MPX 5050GP sensor as a positive pressure sensor. Requires a maximum pressure of 300 mmHg. This tool is also equipped with a SD Card as external storage. The display used in this module is TFT Nextion 2.8”. After conductings measurements of the three comparisons consisting of Multifunction, DPM and mercury tensimeter to 6 times, the smallest result 0 mmHg and the largest results 251.52 mmHg. While the error in mercury tensimeter’s of leak test to module and rigel is 0.56% and 0.404%.